2020
DOI: 10.1021/acsami.0c09082
|View full text |Cite
|
Sign up to set email alerts
|

P2-Type Layered Na0.75Ni1/3Ru1/6Mn1/2O2 Cathode Material with Excellent Rate Performance for Sodium-Ion Batteries

Abstract: Layered oxides acting as sodium hosts have attracted extensive attention due to their structural flexibility and large theoretical capacity. However, the diffusion of Na ions always presents sluggish kinetics due to the larger ionic radius sand mass of Na compared to Li. Herein, we report a P2-type layered cathode material, namely, Na 0.75 Ni 1/3 Ru 1/6 Mn 1/2 O 2 with superfast ion transport, where the Na + diffusion coefficient is calculated mainly in the region of 10 −10 to 10 −11 cm 2 s −1 during the charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 46 publications
(46 reference statements)
8
23
0
Order By: Relevance
“…Upon charging and discharging, no shifts were observed in the binding energy in the whole range. This finding is consistent with the XANES (Figure 4c) and EXAFS (Figure 4d) data that Ru was retained its valance state constantly as 5+ during the first cycle in the voltage range 2-4.1 V, agreeing with the data reported by Zhou et al [43,46] Moreover, we tested the present Na[Ni In addition, the valence of Ru is dependent on the chemical composition. In our case of O3 type Na[Ni 2/3 Ru 1/3 ]O 2 , Ni is divalent, so that Ru is spontaneously stabilized as 5+.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Upon charging and discharging, no shifts were observed in the binding energy in the whole range. This finding is consistent with the XANES (Figure 4c) and EXAFS (Figure 4d) data that Ru was retained its valance state constantly as 5+ during the first cycle in the voltage range 2-4.1 V, agreeing with the data reported by Zhou et al [43,46] Moreover, we tested the present Na[Ni In addition, the valence of Ru is dependent on the chemical composition. In our case of O3 type Na[Ni 2/3 Ru 1/3 ]O 2 , Ni is divalent, so that Ru is spontaneously stabilized as 5+.…”
Section: Resultssupporting
confidence: 92%
“…Therefore, it is concluded that the average oxidation state of Ru may vary from 4+ to 5+ depending on structure and chemical composition, and Ru can be electroactive and nonelectroactive regardless of its initial oxidation state (Table S2, Supporting Information). [34,42,43,[46][47][48][49] Turning to the oxygen redox activity in this material, the O K-edge spectrum was measured and XPS analysis was performed for Na[Ni 2 ). In addition, the peroxo-related peak was still visible during discharge to 3 V and disappeared at 2 V, meaning that the oxidized lattice oxygen was reduced to O 2− in the Na[Ni 2/3 Ru 1/3 ]O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between TM composition and reversible anionic redox in Li-rich layered oxides (Li 2 TMO 3 ) has been extensively reported and elucidated. By correlating the oxygen frequency shifts observed in the phonon density of states along Li 2– x TMO 3 delithiation (TM = Ru, Ni, and Mn) to the nature of the TM–O chemical bond, Shao-Horn and co-workers have unveiled that lattice dynamics can affect both ion mobility and structural stability; they clarified that these effects can be successfully restrained in highly covalent TM oxides. , The presence of Ru in such Li-rich materials seems to be a key enabler to accomplish a reversible access of oxygen redox . Not only do the electronic signatures of reversible O–O coupling in Li 2– x RuO 3 at ∼4.2 V versus Li + /Li represent direct evidence of lattice oxygen redox activated at high voltage, but also the oxygen dimerization mechanism in Ru-doped Li 2 TMO 3 is shown to be hampered compared to other TM doping. , Despite being few, the scientific reports on the use of Ru-doped NIB cathodes have shown promising results . Of course, from the perspective of sustainability and low-cost, it is crucial to find an optimal balance between the Ru amount employed and the possible benefits on the overall cell performances.…”
Section: Introductionmentioning
confidence: 99%
“…If the materials and systems for SIBs outperform LIBs, the replacement of LIBs with SIBs is expected. Recently, a number of studies have been performed to find suitable electrode materials and electrolytes for sodium ion batteries. The separator, as a vital component for SIBs, has not yet been thoroughly and systematically investigated.…”
Section: Introductionmentioning
confidence: 99%